FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI - Kahar, Kartini; Majid, Jamaluddin; Fadhilatunisa, Della (ISAFIR: Islamic Accounting and Finance Review, 2022)
This study aims to show the effect of human resource competence, utilization of information technology and managerial control on the quality of the financial reports of the Takalar Regency Government with organizational commitment as moderating. This research uses quantitative research with descriptive paradigm. The data used is primary data. The research population is the Regional Government of Takalar Regency. The sampling technique used was purposive sampling with a total sample of 85 people. Data analysis used multiple linear regression analysis and moderated regression analysis with absolute difference value approach. The results of this study indicate that the competence of human resources, utilization of information technology and managerial control have a significant positive effect on the quality of financial reports. Organizational commitment is not able to moderate the variables of human resource competence and the use of information technology on the quality of financial reports, but organizational commitment is able to moderate the managerial control variables on the quality of financial reports. This research is practically expected to be an input to improve the quality of financial reports by increasing KSDM, information technology and managerial control. And theoretically it is expected to add to the accounting research literature related to LKPD.